2010
DOI: 10.1115/1.4001632
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Scaling Parameter for Pool Boiling Heat Transfer

Abstract: Although the effects of microgravity, earth gravity, and hypergravity (>1.5 g) on pool boiling heat flux have been studied previously, pool boiling heat flux data over a continuous range of gravity levels (0–1.7 g) was unavailable until recently. The current work uses the results of a variable gravity, subcooled pool boiling experiment to develop a gravity scaling parameter for n-perfluorohexane/FC-72 in the buoyancy-dominated boiling regime (Lh/Lc>2.1). The heat flux prediction was then validated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…The study of Macro et al (Di Marco and Grassi, 2002) about pool boiling under different gravitational accelerations showed that bubbles became smaller at high gravity, and they grew bigger at low gravity. Similar results could also be found in the simulation by Ma et al (2017) and experiments by Raj et al (2010). Besides, the gravity influences on CHF have also been studied in previous research studies (Raj et al, 2010;Ma et al, 2017;Fang et al, 2019), and the results showed that higher gravity within a certain range could increase CHF.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The study of Macro et al (Di Marco and Grassi, 2002) about pool boiling under different gravitational accelerations showed that bubbles became smaller at high gravity, and they grew bigger at low gravity. Similar results could also be found in the simulation by Ma et al (2017) and experiments by Raj et al (2010). Besides, the gravity influences on CHF have also been studied in previous research studies (Raj et al, 2010;Ma et al, 2017;Fang et al, 2019), and the results showed that higher gravity within a certain range could increase CHF.…”
Section: Introductionsupporting
confidence: 84%
“…Similar results could also be found in the simulation by Ma et al (2017) and experiments by Raj et al (2010). Besides, the gravity influences on CHF have also been studied in previous research studies (Raj et al, 2010;Ma et al, 2017;Fang et al, 2019), and the results showed that higher gravity within a certain range could increase CHF.…”
Section: Introductionsupporting
confidence: 84%
“…The heat fluxes for the two larger sizes were comparable at the same wall temperature, while a non-departing primary bubble was formed on 0.81 Â 0.81 mm 2 . The recent experiments conducted by Raj [4] at 1.7 g e using three heater sizes are in consistency. Hence, it was concluded that below the particular heater size, boiling is dominated by surface tension and the nucleate boiling curve is heater-size-dependent.…”
Section: Introductionmentioning
confidence: 54%
“…Refs. [6][7][8]. Boiling has been found to be buoyancy-dominated for heaters above a certain minimum size and to be surface-tension-dominated below this minimum heater size.…”
Section: Introductionmentioning
confidence: 99%